(untitled) (Politeja, 2015)
Russian Aggression Against Ukraine: Political, International – Legal And Economic Consequences Russian military aggression against Ukraine was the culmination of inter-civilizational confrontation of Russia with the West for the final consolidation of spheres of influence in Europe and the world in terms of transformation of international relations from a unipolar to a multipolar system. An important interest for Russia in this confrontation is to return it to the status of a world power. Revolutionary changes in Ukrainian society led to democratization, desovietization and consolidation of the Ukrainian nation. The immediate reaction on this revolutionary process was the Russian military aggression against Ukraine. The military aggression against Ukraine was carried out in the form of a hybrid war. The basic composition of Russian hybrid war in Donbas was inspired internal conflict in Ukraine between the center and the separatist regions. The distinction of Donbas hybrid version of the war is to use armed terror, high intensity combat operations, maneuver their character and widespread use of heavy weapons fire power. The annexation of the Crimea and the occupation of Donbas by Russian troops have a number of consequences that negatively affect international relations and modern system of international law. Aggression of leading to the erosion of the foundations of world order and international security, which could lead to the destruction of the existing world order.